2015
DOI: 10.1177/2324709615612847
|View full text |Cite
|
Sign up to set email alerts
|

Stress Cardiomyopathy in the Setting of COPD Exacerbation

Abstract: Introduction. Stress cardiomyopathy, or takotsubo cardiomyopathy, is an acute, reversible left ventricular dysfunction usually initiated by a psychological or physical stress. We report this case of stress cardiomyopathy following a chronic obstructive pulmonary disease exacerbation and the subsequent treatment. Case Description. A 49-year-old white female with a history of chronic obstructive pulmonary disease presented to the emergency room via emergency medical services with worsening severe shortness of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…[1][2][3][4] The dynamic ST/T alterations on ECG in the inferior and lateral leads without reciprocal ST depression in the other leads are the typical feature of TTC, in the absence of epicardial coronary artery disease, pheochromocytoma, or myocarditis. [1,2] Although the exact pathophysiological pathway of TTC still remains unclear, catecholamine-mediated myocardial stunning including an acute multi-vessel coronary spasm and coronary microcirculation dysfunction has been suggested to play a key role.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[1][2][3][4] The dynamic ST/T alterations on ECG in the inferior and lateral leads without reciprocal ST depression in the other leads are the typical feature of TTC, in the absence of epicardial coronary artery disease, pheochromocytoma, or myocarditis. [1,2] Although the exact pathophysiological pathway of TTC still remains unclear, catecholamine-mediated myocardial stunning including an acute multi-vessel coronary spasm and coronary microcirculation dysfunction has been suggested to play a key role.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Exposure to emotional or physical stress and exaggerated sympathetic activity leads to secretion of excessive catecholamine production and, therefore, it has been suggested that those catecholamine molecules are directly related with myocardium injury. [4] Elevated catecholamine levels decrease the viability of myocytes through cyclic-AMP mediated calcium overload, resulting in contraction band necrosis which is a histological pattern of myocardium injury seen in stress cardiomyopathy. [4] On the other hand, hypoxia and hypercarbia may play an important role in the pathophysiology of TTC using both peripheral and central chemoreceptors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations